Social support perceived by cancer patients and its relation with social and demographic characteristics - Adriane Cristina Bernat KOLANKIEWICZ; Marina Mazzuco de SOUZA; Tânia Solange Bosi de Souza MAGNAGO; Edvane Birelo Lopes DE DOMENICO
To analyze the relation between social support and socio-demographic characteristics of oncology patients. Transversal study, developed with oncology patients living in the Ijuí city, Rio Grande do Sul state, Brazil between July and December 2012, the population was selected through convenience. For data collection we used the Brazilian version of the Social Support Scale and the Medical Outcomes Study data were analyzed with descriptive statistics resources and analytical. Average scores on the dimensions were: 82,36±24,42 (positive interaction), 85,39± 19,81(information), 87,98±18,68 (emotional support), 88,52±18,56 (material support) and 93,50±14,44 (affective support). Evidences showed higher averages in male mulattos patients (p<0,05). There was a direct and growing relationship between per capita income, social support and affective positive interaction. It was proven that patients receive social support in all dimensions, with high scores, but with variations, considering the characteristics of gender, civil status, educational level, per capita income and race.